Network Meta-Analysis of Wound Dressings and Their Effectiveness in Promoting Healing - Burhan, Asmat; Susanti, Indah; Silva, Vanessa A Breu Da; Kumar, Vijay; Kim Chi, Do Thi; Hidayat, Riski; Sebayang, Septian Mixrova; Hamka, Hamka (Department of Nursing, Faculty of Medicine, Universitas Diponegoro, 2025)
Background: Chronic and acute wounds affect millions of individuals worldwide, placing a substantial burden on patients and healthcare systems. Previous evaluations have often focused on limited types of dressings or specific wound conditions. Therefore, a comprehensive network meta-analysis is essential for comparing various interventions, bridging knowledge gaps, improving healing outcomes, and addressing clinical and economic challenges.Purpose: This study assessed the comparative effectiveness and safety of advanced wound dressings in promoting healing.Methods: This network meta-analysis, registered with PROSPERO (CRD42023433268), systematically searched PubMed, ProQuest, Scopus, CINAHL, ScienceDirect, Springer Nature, Wiley, Cochrane Library, and Taylor & Francis from January 2012 to December 2022. Eight reviewers independently assessed and extracted data from randomized controlled trials evaluating different dressings, including placebo, alginate, collagen, gamat, honey, hyaluronic acid, hydrocolloid, hydrogel, mebo, platelet-rich plasma, povidone-iodine, and silver sulfadiazine. Data were synthesized using a random-effects network meta-analysis with SUCRA rankings. Study quality was evaluated using Cochrane RoB2, and certainty of evidence was assessed through CINeMA.Results: This review included 38 RCTs with a total of 4,049 patients. The largest placebo group comprised 1,628 participants, while the smallest group was mebo with 10 participants. Heterogeneity and consistency analysis showed negligible variation (χ²=1.757, p=0.78). Alginate dressings were the most effective in reducing wound size compared to placebo (OR 0.64; 95% CI 0.38–1.08; SUCRA probability 0.73), whereas hyaluronic acid dressings were the least effective (OR 0.22; 95% CI 0.06–0.79; SUCRA probability 0.08).Conclusion: Alginate was identified as the most effective primary dressing for wound healing, while hyaluronic acid dressings were the least effective. However, clinical practitioners should carefully weigh the benefits and limitations of each dressing type before selecting the most appropriate treatment for patients.